2014
DOI: 10.1038/ki.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

The case for 0.9% NaCl: is the undefendable, defensible?

Abstract: Although 0.9% NaCl solution is by far the most-used fluid for fluid therapy in resuscitation, it is difficult to find a paper advocating its use over other types of crystalloid solutions. Literature on the deleterious effects of 0.9% NaCl has accumulated over the last decade, but critical appraisal of alternative crystalloid solutions is lacking. As such, the literature seems to suggest that 0.9% NaCl should be avoided at all costs, whereas alternative crystalloid solutions can be used without scrutiny. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 93 publications
0
20
0
2
Order By: Relevance
“…The most used fluid in resuscitation, i.e. 0.9% NaCl, has been especially implicated in this respect and its use as a resuscitation fluid is a subject of controversy [30,31]. It is clear, however, that the administered volume is the key issue that determines the extent to which fluid therapy is deleterious to renal function.…”
mentioning
confidence: 99%
“…The most used fluid in resuscitation, i.e. 0.9% NaCl, has been especially implicated in this respect and its use as a resuscitation fluid is a subject of controversy [30,31]. It is clear, however, that the administered volume is the key issue that determines the extent to which fluid therapy is deleterious to renal function.…”
mentioning
confidence: 99%
“…NS infusions have been associated with greater chloride administration and high rates of resultant renal dysfunction in some cases [1,11]. On the contrary, recent evidences in both the critical and noncritical care setting (with both small and large volume infusions), have suggested that there is no significant difference in severe AKI rates when comparing NS to a balanced crystalloid solution [2,7,8,10]. Our data add to the literature investigating the effects of intravenous infusions on AKI incidence.…”
Section: Discussionmentioning
confidence: 35%
“…2018;7(2):39-44 also further exploring the effects of infusing NS with lower volumes (typically volumes less than 3 L per 24 h), than in the critically ill population [1,2]. Our study therefore aimed to investigate any significant biochemical effects of maintenance intravenous NS infusions compared to a buffered crystalloid solution, compound sodium lactate (CSL), in acute general medical and surgical patients with a variety of diagnoses.…”
Section: Fluids In Acute Medical and Surgical Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Сбалансированные солевые растворы (растворы с физиологическим значением рН и изотонической концентрацией электролитов), будучи более физио-логичными, используются чаще, в том числе в каче-стве среды, несущей коллоид [12]. Сбалансированные растворы по солевому составу идентичны человече-ской плазме, имеют более низкое содержание натрия и хлорида, чем 0,9% раствор хлорида натрия, и добав-ление в качестве буферного раствора ацетата или лак-тата.…”
Section: научный обзор / Scientific Reviewunclassified